Clinical and Neuroimaging Changes in Ephedrine Abusers - Severyn, Iu. (Psychiatry, Neurology and Medical Psychology, 2016)
The given article conserns the problem of homemade ephedrine drugs. It is shown that the use of these substances leads to serious changes in the brain by MRI data. The presence of Parkinson’s syndrome, pyramidal, cerebellar, oculomotor and autonomic disturbances, cognitive and depressive disorders during the neurological examination were revealed. Doctors shoul be alert to identify mentioned symptoms in young people conserning taking drug for the purpose of providing timely assistance and adequate correction of violations.